Holiness and Power Constantinopolitan Holy Men and Authority in the 5th Century - Kosinski, Rafal (Millennium-Studien / Millennium Studies, 2016)
The book examines models of relationships between Constantinopolitan holy man and secular and ecclesiastical authorities in the capital of Byzantium. The study explores the ideal underlying the lives of the four Constantinopolitan holy men (Hypatios, Alexander Akoimetos, Daniel the Stylite, Marcellus Akoimetos), which was a reflection of contemporary reality as well as a vision of an ideal state.